Les Habsbourg en Europe Circulations, échanges, regards croisés - Merle, Alexandra; Leroy du Cardonnoy, Eric (Studia Habsburgica, 2018)
This volume, which focuses on the relations between the two branches of the Habsburg dynasty in the modern era, examines the ways in which identity was constructed exploring the idea of a joint policy of the House of Austria in Europe. It also examines, through various case studies, the movement through the Habsburg possessions of individuals who belonged not only to the elite but to a variety of social and professional circles - artists, ecclesiastics, merchants and scholars. Ce volume consacré aux relations entre les deux branches de la dynastie de Habsbourg à l'époque moderne s'intéresse aux modalités d'une construction identitaire et soumet à l'analyse l'idée d'une politique conjointe de la Maison d'Autriche en Europe, avant d'aborder, à travers quelques études de cas, la circulation à travers les possessions des Habsbourg d'individus appartenant non pas aux seules élites mais à des milieux sociaux et professionnels variés - artistes, ecclésiastiques, marchands et savants.